REITERATIVE (m_n)-DISTRIBUTIONAL CHAOS FOR BINARY RELATIONS OVER METRIC SPACES - Kostić, Marko; Velinov, Daniel (Matematichki Bilten, 2019)
This paper intends to be a heuristical study. Let \((m_n)\) be an increasing sequence in \([1,∞)\) satisfying \(_n→∞m_nn>0\), \(λ(0,1]\), \(s{0,1-,1+,2-}\) and \(iN[1,20]\). We introduce and analyze the concepts of reiterative \((m_n,X)\)-distributional chaos of type \(s\), reiterative \((λ,X)\)-distributional chaos of type \(s\), reiterative \([X,m_n,i]\)-distributional chaos and reiterative \([X,λ,i]\)-distributional chaos for general sequences of binary relations over metric spaces.